An optimized protocol to determine the engulfment of cancer cells by phagocytes using flow cytometry and fluorescence microscopy - Nam, Gi-Hoon; Hong, Yeonsun; Choi, Yoonjeong; Kim, Gi Beom; Kim, Yoon Kyoung; Yang, Yoosoo; Kim, In-San (ELSEVIER, 2019)
The engulfment of cancer cells by macrophages is an important cellular process in innate cancer immunity. Antitumor immunotherapy that utilizes the enhanced engulfment of cancer cells by phagocytic cells has attracted much attention. Therefore, there is a growing demand for methods of measuring cancer cell phagocytosis. Quantifying the various stages of phagocytosis is invaluable for elucidating cancer-immune responses during this process. Here, we describe two phagocytosis assays, a flow cytometric assay and a fluorescent microscopic assay; the flow cytometric method utilizing CellTracker dye provides a simple, measurable, and highly reproducible functional assay to measure the phagocytosis efficiency of cancer cells by bone marrow-derived macrophages. As an alternative method of evaluating various states of cancer cell phagocytosis, a fluorescent microscopic method that employs a pH-sensitive dye (pHrodo-SE dye) is also described in this paper. Image-based analysis using this labeling approach enables researchers to measure phagocytic indices that indicate the number of cancer cells engulfed by each macrophage. We have highlighted that these assays can be applied to multiple tumor types and used as selection tools for a variety of phagocytosis agonist types. The results of this study may facilitate a better understanding of the interactions between tumor cells and phagocytes, which could lead to the identification of new therapeutic targets against cancer.
Keywords: MACROPHAGES